Steroid Receptor Coactivators as Therapeutic Targets in the Female Reproductive System - Szwarc, Maria M. (J Steroid Biochem Mol Biol, 2015)
The Steroid Receptor Coactivators (SRCs/p160/NCOA) are a family of three transcriptional coregulators initially discovered to transactivate the transcriptional potency of steroid hormone receptors. Even though SRCs were also found to modulate the activity of multiple other transcription factors, their function is still strongly associated with regulation of steroid hormone action and many studies have found that they are critical for the regulation of reproductive biology. In the case of the female reproductive tract, SRCs have been found to play crucial roles in its physiology, ranging from ovulation, implantation, to parturition. Not surprisingly, SRCs’ action has been linked to numerous abnormalities and debilitating disorders of female reproductive tissues, including infertility, cancer, and endometriosis. Many of these pathologies are still in critical need of therapeutic intervention and “proof-of-principle” studies have found that SRCs are excellent targets in pathological states. Therefore, small molecule modulators of SRCs’ activity could be applied in the future in the treatment of many diseases of the female reproductive system.